2018
DOI: 10.3389/fpubh.2018.00123
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Residential Mental Health Recovery Service in North Queensland

Abstract: BackgroundEvidence shows that subacute mental health recovery occurs best when a person remains active within the community and fulfils meaningful and satisfying roles of their choosing. Several residential care services that incorporate these values have been established in Australia and overseas.AimsThis study describes (a) the development of an evaluation framework for a new subacute residential mental health recovery service in regional Australia and (b) reports on the formative evaluation outcomes.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 12 publications
2
18
1
Order By: Relevance
“…Further, the involvement of families and carers is highlighted in the Victorian Framework for recovery-oriented practice (39), and this may have particularly influenced PARC services which emphasize recovery-oriented care. The many obstacles and challenges to family-inclusive practice and widespread culture change needed to embed this practice have been identified (15, 38), but we did not find that the local MHCSS service operator was a factor which distinguished between clusters in this regard. Our finding concerning family invitations to care meetings may also speak to increasing social openness of the PARC services.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Further, the involvement of families and carers is highlighted in the Victorian Framework for recovery-oriented practice (39), and this may have particularly influenced PARC services which emphasize recovery-oriented care. The many obstacles and challenges to family-inclusive practice and widespread culture change needed to embed this practice have been identified (15, 38), but we did not find that the local MHCSS service operator was a factor which distinguished between clusters in this regard. Our finding concerning family invitations to care meetings may also speak to increasing social openness of the PARC services.…”
Section: Discussioncontrasting
confidence: 68%
“…The PARC services framework and operational guidelines were developed by the Victorian government Department of Health (now known as the Department of Health and Human Services, DHHS) to support service planning and delivery (9). Several uncontrolled, quasi-experimental or small mixed-methods studies of the Victorian PARC service model or equivalents in other states have suggested improved symptomatic, functional and recovery outcomes for consumers, although findings are mixed concerning reductions in psychiatric bed usage (1015).…”
Section: Introductionmentioning
confidence: 99%
“…It has been well established that the therapeutic relationship is an important facilitator of recovery for both young people and adults with aspects such as trust, respect and ‘caring’ being important to both [17, 18, 60]. However, the value placed on a friendship-like relational experience with staff among young people tends to be less prominent in studies with adults [20].…”
Section: Discussionmentioning
confidence: 99%
“…Provision of sub-acute residential services for adults has become increasingly common in Australia [17, 20, 21]. Recovery-oriented models of care are embedded into many of these [19, 22–24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation